EKSISTENSI MEDIA DALAM PEMBELAJARAN MELALUI MEDIA SOSIAL DAN MEDIA AUDIOVISUAL DI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN (FKIP) UNIVERSITAS PRIMA INDONESIA - Rony Arahta Sembiring; Ermina Waruwu (Universitas Negeri Medan, 2020)
This study aims to identify learning outcomes through the media used by students, focus student knowledge to determine the contribution of media in their learning, improve student expertise / knowledge, and provide opportunities for students to become innovative teachers. This research method applies descriptive qualitative data analysis and comparative quantitative. The research data was measured through test and non-test instruments. The research sample was FKIP students majoring in Indonesian and English through 2 general subjects, namely learning media and educational statistics. The results of the study have shown that the learning outcomes of the two majors do not show a significant difference. Furthermore, 24 questionnaire items showed that social media contributed more to student learning activities than audiovisual media. On the other hand, the observations show that students are more likely to behave negatively during research activities. Students feel uncomfortable if learning activities are dominated by media. Plus the imposition of online learning which requires virtual learning activities. So this research concludes that the existence of the media will be increasingly felt if it is collaborated with other relevant learning methods.Keywords: Media, Learning, Existence, FKIP Students